(untitled) (Neo Scientific Peer Reviewed Journal, 2023)
Diabetic nephropathy is one of the most common causes of terminal chronic renal failure (ESRD). Over the past decade, in the USA and a number of countries in Europe and Asia, DN has reached the 1st place in terms of the need for replacement therapy for renal insufficiency. According to epidemiological studies, the prevalence of DN in type 2 diabetes in the Russian Federation is 39.3-40.6%. The risk of kidney damage in patients with type 2 diabetes, according to many authors, depends on the duration of the disease. With a duration of DM 10-15 years, the frequency of DN is 15-20%, 20 years - 20-35%, and with a longer course of DM - up to 50%. A feature of kidney damage in type 2 diabetes is the absence of pronounced clinical symptoms at the beginning, which is the reason for its late diagnosis.